Vermiophis luqianlei sp. nov., a new species of wormlion fly (Diptera: Vermileonidae) from Guizhou, China, with notes on its immature stages and biology - Sun, Yan; Li, Jia-Ling; Wang, Ji-Shen (Zootaxa, 2026)
The genus Vermiophis Yang, 1979 is endemic to China and previously comprised eight known species. In the present study, a new species, Vermiophis luqianlei sp. nov., from Xishui, Guizhou, China, is described. This new species closely resembles V. wudangensis Yang & Chen, 1986, but differs from it in several key characters, including wing venation and genital morphology. This paper also illustrates and describes the immature stages of the new species, provides an updated key to all nine currently known species of Vermiophis, and discusses the biology and systematic implications of the new species.